Effect of temperature and various pre-treatments on seed germination parameters of Stachys circinata and Stachys saxicola subsp. platyodon - Amal Maurady; Soumaya El Ismaili; Mohammed Reda Britel; Abdelmonaim Homrani Bakali (African and Mediterranean Agricultural Journal - Al Awamia)
In order to contribute to the conservation and valorization of two vulnerable Moroccan medicinal plants, Stachys circinata and Stachys saxicola subsp. platyodon, this study aims to identify optimal germination conditions under which we can improve their germination performance. Seven pre-treatments were tested at 25/10 °C, including pre-soaking in cold water and gibberellic acid (GA3) solutions (250 and 500 mg/l), mechanical scarification and two combined treatments (cold stratification for 15 days with 500 mg/l GA3 and mechanical scarification with pre-soaking in water for 24 h). Seeds were then exposed to seven alternating temperature regimes (10/0, 15/05, 20/10, 25/10, 30/15, 35/20 and 40/25 °C) with a 14/10 h light/dark photoperiod. Results showed that the highest germination percentage (73%) and shortest mean germination time (MGT) (10.4 days) for S. circinata seeds were obtained at 20/10 °C. For S. saxicola subsp. platyodon, the highest germination percentage was registered at 15/05 °C (65%), but seeds germinate more quickly at 20/10 °C. No germination was observed at low and high temperature regimes (10/0 and 40/25 °C, respectively) for both species. Germination capacity was improved by mechanical scarification in S. circinata (75% vs 60% for control), while for S. saxicola subsp. platyodon, it was improved by GA3 treatment at 250 mg/l (52.5% vs 35.0% for control). Germination speed of both species was positively increased by GA3 treatment. These results may be useful for domestication and/or conservation efforts of these two endemic species.